A study on factors contributing to employee motivation in Bank Simpanan National, Masjid Jamek Branch, Kuala Lumpur / Muhammad Suhaimi Sulaiman and Nur ‘Aina Al Mardhiah Said - Sulaiman, Muhammad Suhaimi; Said, Nur ‘Aina Al Mardhiah (Faculty of Administrative Science and Policy Studies, 2014)
This research is about a study on factors contributing to employee motivation in Bank Simpanan Nasional at Masjid Jamek Branch, Kuala Lumpur. The purpose of this research is to determine whether there is any relationship between receiving high salary and employee motivation, to determine whether there is any relationship between working environment and employee motivation, to identify whether there is any relationship between receiving employer’s recognition and employee motivation and lastly to identify the factor that influences employee motivation the most in BSN Masjid Jamek Branch, Kuala Lumpur. Based on this research, there are four factors that contribute to employee motivation which are recognition from employer, working environment and high salary. This research represents motivation in Bank Simpanan Nasional at Masjid Jamek Branch, Kuala Lumpur. In this organization, it consists of 6 departments which are Department of Strategic Communications, Department of Micro Finance, Department of Management Services and Debt Recovery, Department of Credit Retail Operations, Department of Information Technology, and Department of Treasury and Investment. Only 127 respondents were selected using simple random sampling out of 200 employees. Based on this research, working environment shows the most significant relation which means working environment contribute the most on employee motivation in Bank Simpanan Nasional at Masjid Jamek Branch, Kuala Lumpur.